The Effect of Using Instagram Influencers in Building Conseva’s Brand Awareness - Paulina Tjandrawibawa (Bina Nusantara University, 2020)
Rapid growth of social media development leads to abundant brands’ promotion for their products or services. One of the many ways is promotion through influencers on Instagram. Recently, it is known that companies using Influencer marketing tend to keep going up since such particular way is considered to be quite effective to increase brand awareness. However, the average data obtained from various journals and articles is data from medium to large scale companies both locally and internationally. Therefore, this study was conducted to examine whether the use of Instagram influencers to increase brand awareness is also effective for micro-scale local brands by taking examples from one of Surabaya lifestyle brands called Conseva. This research was conducted with a quantitative method focusing on collecting numerical data to see the results of the growth of followers and visits obtained by Conseva before and after using Instagram influencers. If the number of Instagram followers and visits to Conseva increases, it means that brand awareness has also increased and vice versa.